Preserving the Digital Record: Challenges in Archiving Born-Digital Content and Big Data - Bayu Hartono; Ahmed Al-Mohannadi; Ana María Rodríguez (Journal of Loomingulisus ja Innovatsioon, 2026)
The rapid expansion of digital technologies has led to an unprecedented growth in born-digital content and big data, presenting new challenges for long-term preservation. Born-digital content, including emails, websites, and social media posts, requires specialized strategies for archiving due to its format volatility and ephemeral nature. Similarly, the vast and complex nature of big data poses significant difficulties in ensuring data integrity, security, and accessibility over time. This study aims to explore the challenges in archiving born-digital content and big data and to evaluate the current practices and frameworks employed by organizations in managing these digital records. A mixed-methods approach was used, combining qualitative interviews with digital archivists and quantitative surveys from organizations across sectors like government, academia, and technology. The results reveal a widespread reliance on cloud storage, with limited use of specialized archival systems for big data. Additionally, 15% of organizations lack a formal digital preservation strategy. The study concludes that while cloud storage offers scalability, specialized archival solutions are essential for long-term preservation, especially for big data. The research highlights the need for standardized frameworks and advanced technologies to address the growing complexities of digital preservation.